Republic of Moldova : Fourth Reviews Under the Extended Arrangement and Under the Three-Year Arrangement Under the Extended Credit Facility, and Requests for Waiver for Nonobservance of a Performance Criterion and for Modification of a Performance Criterion: Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2012)
Moldova's near-term outlook is aimed at slowing growth and receding inflation, but the deteriorating external environment and the fragile political situation poses significant downside risks. The main drivers of growth are private consumption, investment, and exports, fuelled by remittances and rising credit, which is reflected in the improving business climate. Weak tax collection and expenditure overruns resulted in missing the performance criterion on the general government budget deficit by 0.4 percent of GDP. The indicative target on reducing general government expenditure arrears was missed marginally owing to underpayment of heating bills by the Chisinau municipality.